2021
DOI: 10.3920/jiff2020.0063
|View full text |Cite
|
Sign up to set email alerts
|

Insect left-over substrate as plant fertiliser

Abstract: The production of insect protein as human food and livestock feed (entomophagy) may provide a more environmentally beneficial alternative to traditional animal agriculture. However, the resulting waste product from insect production has resulted in large accumulations of left-over substrate and frass. Due to its nutrient and microbial profile, this left-over product has the potential to be utilised as a biofertiliser for high value crop production. Studies have been conducted using the frass of various insects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…Insects are capable of consuming animal manure, and /food wastes, and reducing pollution, and providing protein (larvae), and fertilizer (frass). Insects converts waste into proteins, and reduces total nitrogen concentrationexcretion, odors, and methane emission, thus reduces up to 80% of waste mass [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Insects are capable of consuming animal manure, and /food wastes, and reducing pollution, and providing protein (larvae), and fertilizer (frass). Insects converts waste into proteins, and reduces total nitrogen concentrationexcretion, odors, and methane emission, thus reduces up to 80% of waste mass [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The left-over substrates from insect mass-rearing farms can be used to promote plant growth and health, the latter probably through chitin (Chavez and Uchanski, 2021). They also indicated that levels of bioavailable phosphorous (P) in insect frass are high, which is important considering the limited availability of P for agriculture in the future.…”
Section: Organic Side Streams To Rear Insectsmentioning
confidence: 99%
“…Mass rearing of insects could be a sustainable and ecological alternative for animal protein production [2]. However, the insect farming activity generates large amounts of excreta called insect frass [3]. The use of these frass as biofertilizers could represent an opportunity to decrease the use of chemical fertilizers and thus contribute to the development of resilient and sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%